2011
DOI: 10.1001/archsurg.2011.6
|View full text |Cite
|
Sign up to set email alerts
|

Early vs Interval Appendectomy for Children With Perforated Appendicitis

Abstract: Setting: A tertiary-referral urban children's hospital.Patients: A total of 131 patients younger than 18 years with a preoperative diagnosis of perforated appendicitis.Interventions: Early appendectomy (within 24 hours of admission) vs interval appendectomy (6-8 weeks after diagnosis).Main Outcome Measures: Time away from normal activities (days). Secondary outcomes included the overall adverse event rates and the rate of predefined specific adverse events (eg, intra-abdominal abscess, surgical site infection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
96
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(101 citation statements)
references
References 30 publications
2
96
2
1
Order By: Relevance
“…This differentiation has clinical implications, as new data suggest that antibiotic therapy alone may be adequate treatment for nonperforated appendicitis in children [22]. As a randomized trial found that nonoperative management of perforated appendicitis with an associated phlegmon in children results in worse outcomes than primary operative management, the ability to distinguish simple from perforated appendicitis is critical if practice patterns eventually trend away from operative management of simple appendicitis [23].…”
Section: Discussionmentioning
confidence: 99%
“…This differentiation has clinical implications, as new data suggest that antibiotic therapy alone may be adequate treatment for nonperforated appendicitis in children [22]. As a randomized trial found that nonoperative management of perforated appendicitis with an associated phlegmon in children results in worse outcomes than primary operative management, the ability to distinguish simple from perforated appendicitis is critical if practice patterns eventually trend away from operative management of simple appendicitis [23].…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Early diagnosis of appendicitis is important because of the increased morbidity, mortality, and costs associated with perforated appendicitis. 5,6 Although there is no diagnostic gold standard for appendicitis, 2 grading scores, the Alvarado and Samuel' s pediatric appendicitis score (PAS), have been developed to aid accurate diagnosis of appendicitis. 1,[7][8][9] The PAS is a score that was first reported by Samuel in Journal of Pediatric Surgery in 2002.…”
mentioning
confidence: 99%
“…The risk of perforation is highest in the first 4 years of life and was reported in more than 70% of children in this age group. By comparison, the rate of perforation in adolescents is 10-20% reported by the authors [15,16].…”
Section: IVmentioning
confidence: 92%
“…Later appendectomy patients stayed in the hospital two days longer, and 87 percent received a central venous catheter, compared with only 44 percent of patients who had the early operation. Of all patients who received catheters, 43 percent of later appendectomy patients were discharged with it, compared with only 9 percent of early appendectomy patients by [16].…”
Section: IVmentioning
confidence: 99%
See 1 more Smart Citation